2020
DOI: 10.7554/elife.58771
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased homeologous recombination during pneumococcal transformation allows for multiple chromosomal integration events

Abstract: The spread of antimicrobial resistance and vaccine escape in the human pathogen Streptococcus pneumoniae can be largely attributed to competence-induced transformation. Here, we studied this process at the single-cell level. We show that within isogenic populations, all cells become naturally competent and bind exogenous DNA. We find that transformation is highly efficient and that the chromosomal location of the integration site or whether the transformed gene is encoded on the leading or lagging strand has l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 111 publications
3
17
0
Order By: Relevance
“…Transformation efficiency increased with length of both the overall molecule, and the homologous region (Figure 6A). This is in line with previous studies showing the importance of molecule length and homology in pneumococcal transformation (Kurushima et al, 2020; Morrison and Guild, 1972). We hypothesize that increased length may increase the likelihood of spontaneous contact with the ComGC pilus, while also decreasing the likelihood of homologous region fragmentation by EndA, prior to entry (Morrison and Guild, 1973).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Transformation efficiency increased with length of both the overall molecule, and the homologous region (Figure 6A). This is in line with previous studies showing the importance of molecule length and homology in pneumococcal transformation (Kurushima et al, 2020; Morrison and Guild, 1972). We hypothesize that increased length may increase the likelihood of spontaneous contact with the ComGC pilus, while also decreasing the likelihood of homologous region fragmentation by EndA, prior to entry (Morrison and Guild, 1973).…”
Section: Resultssupporting
confidence: 93%
“…Transformation efficiency increased with length of both the overall molecule, and the homologous region (Figure 6A). This is in line with previous studies showing the importance of molecule length and homology in pneumococcal transformation (Kurushima et al, 2020;Morrison and Guild, 1972). The efficiencies of the short overlapping fragments were lower than that of the long fragments, although increased slightly when transformed in combination.…”
Section: Non-contiguous Recombination Events Likely Results From a Single Donor Moleculesupporting
confidence: 92%
See 1 more Smart Citation
“…Next, an HR template is constructed that consists of the upstream and downstream regions of the deletion target. It has been shown that higher transformation efficiency is observed at higher donor DNA concentrations and with longer homology regions, with a plateau of approximately 1,000 bp of homology ( 34 , 35 ). Therefore, each selected homology arm is designed to be at least 1,000 bp, ensuring efficient homologous recombination.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the transformation efficiency and doubling time of the cells, the total experimental time for Cell-Sens to perform detection of a target DNA sequence was approximately one day. To speed up the DNA detection workflow, flow cytometry or fluorescence microscopy could be used to quantify fluorescent cells within hours following transformation before selection 47 . Future work will investigate the generalizability of the DNA sensor to sensing other organisms beyond bacteria, including viruses, fungi or cancer cells 48 .…”
Section: Discussionmentioning
confidence: 99%